NILAI-NILAI KONSELING PADA PRIBADI KH. ACH HARIRI ABDUL ADHIM - Mawardi; Samsul Arifin; A. Khairuddin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
Guidance counseling services or counseling there are several foundations, principles and asaz that must be considered by a counselor as well as supporting personality values. Therefore, the personality of the counselor becomes a support in the continuation of the process of Islamic counseling guidance services for counselees. This study uses a qualitative approach to the study of figures or often also called research figures or research on individual life history (individual life history). The counselor's personality in KH. Hariri Abdul Adhim namely having a pious, patient, compassionate personality to the santri and communicative. While the behavioral change techniques used by KH. Hariri Abdul Adhim told students to use several techniques, namely the technique of candidate for hasanah or advice, the technique of istikomah in giving uswatun hasanah, men'zir to students who were naughty or violating, giving awards or praise to students who excel and pray for students.